Development of cloud data center simulation environment - Wong, Yit Jian (2018)
Cloud Computing is an emerging technology and is growing more and more popular in business organization due to the cost and time saving benefits. However, the energy consumption of data centers is also drastically increasing over these few years under the growth of Cloud infrastructure. The high amount of energy consumption not only contributes to a major portion of the data center operational cost but also high carbon footprints to the environment. With global climate change and energy shortages leading our concern these days, the energy consumption of data centers has become a key issue for Cloud Computing. Therefore, this project presents a temperature-based scheduler for energy efficient resource allocation in the Cloud Computing Data Centers. The performance evaluation and validation of the proposed algorithm is tested in the GreenCloud simulator environment.